Influence of growth duration to the Zinc Oxide (ZnO) nanorods on single-mode silica fiber - Idris, N. F.; Lokman, Muhammad Quisar; Harun, Sulaiman Wadi; Rahim, H. R.A.; Hasbullah, Nurul Fadzlin; Saidin, Norazlina (Universiti Teknikal Malaysia Melaka, 2018)
Synthesizing Zinc Oxide (ZnO) nanorods by varying the growth duration will give effect to the morphology of ZnO nanorods which were grown by using microwave assisted hydrothermal method. The effect of different growth duration from 4 to 10 hours is investigated on the surface of bare silica optical fiber. The buffer coating of a silica fiber is stripped off for 5 cm to expose the area for the growth of ZnO nanorods. The ZnO nanorods were grown on the fiber by dipping the fiber into the prepared growth solution in a 90˚C microwave assisted hydrothermal synthesised. The physical characterization through field emission scanning electron microscopy (FESEM) results show the diameter of ZnO nanorods is about 75.0 - 93.8 nm and the length of ZnO nanorods ranges from 666.2 nm to 978.6 nm according to their growth duration. The uniform growth of 43.33 nanorods/(µm)2 reveals that the 10 hours of growth duration performs the highest density growth of ZnO nanorods. The amplified spontaneous emission (ASE) peaking at 1550 nm is used to investigate the effect on the light intensity in the optical fiber with coated and uncoated ZnO for optical characterization. The ASE spectrum shows that the light intensity decreases with the growth durations due to the light scattering effect.